2012
DOI: 10.3892/mmr.2012.835
|View full text |Cite
|
Sign up to set email alerts
|

High expression and nuclear localization of β-catenin in diffuse large B-cell lymphoma

Abstract: Abstract. The Wnt/β-catenin signaling pathway plays diverse roles in embryonic development and maintenance of organs and tissues in adults as well as in the pathogenesis of a range of diseases, including many types of carcinomas. β-catenin, the principal downstream effector of the Wnt/β-catenin pathway, migrates to the nucleus and mediates the activation of the Wnt/β-catenin pathway. The aim of the present study was to investigate the expression and localization of β-catenin in diffuse large B-cell lymphoma (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 26 publications
3
11
1
Order By: Relevance
“…The abundance of specific splice variants of FOXP1 is thought to figure prominently in determining its impact on cancer initiation and progression, although the correlative studies of FOXP1 expression in cancer must be interpreted with caution, as most did not quantify isoform-specific expression. Our mouse xenograft study suggests that FOXP1 isoform 1 promotes tumor growth, a result consistent with the oncogenic functions of Wnt signaling in epithelia cancers and lymphoma (44, 51). In agreement with our result, diagnostic chromosomal translocations place the FOXP1 gene downstream of strong immunoglobulin heavy chain ( IG ) promoters in some DLBCL tumors, resulting in increased abundance of FOXP1 isoform 1 (68).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The abundance of specific splice variants of FOXP1 is thought to figure prominently in determining its impact on cancer initiation and progression, although the correlative studies of FOXP1 expression in cancer must be interpreted with caution, as most did not quantify isoform-specific expression. Our mouse xenograft study suggests that FOXP1 isoform 1 promotes tumor growth, a result consistent with the oncogenic functions of Wnt signaling in epithelia cancers and lymphoma (44, 51). In agreement with our result, diagnostic chromosomal translocations place the FOXP1 gene downstream of strong immunoglobulin heavy chain ( IG ) promoters in some DLBCL tumors, resulting in increased abundance of FOXP1 isoform 1 (68).…”
Section: Discussionsupporting
confidence: 79%
“…β-catenin protein abundance positively correlates with DLBCL disease progression, which is consistent with its oncogenic role in many epithelial tumors (44). Therefore, we speculated that FOXP1 might promote Wnt/β-catenin signaling in human DLBCL.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…In line with a previous report, we could detect enhanced β-catenin protein expression in a subset of DLBCL biopsies. 38 However, Ge et al found β-catenin largely in the nucleus of DLBCL cells and we detected predominantly cytosolic staining in the ABC DLBCL cell lines and DLBCL biopsies. The positive β-catenin staining in DLBCL resembled the perinuclear or diffuse localization observed in lymphocytes or chronic lymphocytic leukemia cells.…”
Section: Discussioncontrasting
confidence: 56%
“…FOXP1 is an enhancer of WNT/beta-catenin pathway transduction (Walker et al, 2015). Several studies have shown that WNT/beta-catenin pathway is increased in DLBCLs (Ge, Lv, Feng, Liu, and Wang, 2012;Koch et al, 2014;Qiang, Endo, Rubin, and Rudikoff, 2003;Reya et al, 2000;Staal et al, 2001).…”
Section: Canonical Wnt/beta-catenin Pathwaymentioning
confidence: 99%